Flue gas moisture capacity calculation at the outlet of the condensation heat recovery unit; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Galashov N. N. Nikolay Nikitovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Melnikov D. V. Denis Vladimirovich; Kiselev A. D. Aleksandr Dmitrievich; Gabdullina A. I. Albina Ilgizovna (2017, 2017)
Title screen